Characteristics of Electrodiagnosis in Drop Foot Patients at Neurological Polyclinics - Elsye Anita Umsina Nauw, Haya; Arimbawa, I Komang; Dwita Pratiwi, Ni Made (Rifa'Institute, 2024)
Introduction: Drop foot is the inability to lift the front leg due to the dorsoflexion weakness of the foot, which causes an unsafe gait and potentially results in a fall. This weakness is often caused by compression neuropathy of the peroneal nerve and can result from injuries at various levels of the nervous system. Other causes include metabolic diseases such as diabetes mellitus as well as neurodegenerative, neuromuscular, and inflammatory conditions. The gold standard for diagnosing peroneal neuropathy is electrodiagnostic testing, including nerve conduction studies and needle electromyography, which are useful for detecting lesions and differentiating the degree of lesion in the nervous system. Objective: This study aims to determine the characteristics of drop foot patients who undergo electrodiagnostic examinations, especially the results of Compound Muscle Action Potential (CMAP) and Sensory Nerve Action Potential (SNAP), at the Neurological Polyclinic of Professor IGNG Ngoerah Hospital Denpasar, Bali. Method: This study used a cross-section descriptive study. Data was collected from the medical records of patients who underwent electrodiagnostic examinations at the neurological polyclinic of Professor IGNG Ngoerah Hospital. Data analysis was conducted to evaluate the characteristics of CMAP and SNAP in patients with drop foot complaints. Result and Discussion: the study showed that as many as 80% of drop foot patients were male, electrodiagnostic examination, in CMAP assessed the peroneal and tibial nerves, the motor nerve transmission there were 100% lesions on the peroneal nerve at all levels of lesion location. Meanwhile, different results can be seen from the assessment of SNAP function where what is assessed is the surreal nerve in each different lesion group. Conclusion: Electrodiagnostic examinations, particularly CMAP and SNAP analysis, are effective in identifying peroneal neuropathy as the cause of foot drop. This study supports the importance of electrodiagnostic examination to determine the location of the lesion and plays a role in the treatment and prognosis of patients with drop foot complaints in the neurological polyclinic